KAJIAN KINERJA MESIN PENCAMPURAN PAKAN TERNAK MENGGUNAKAN DAYA 0,25HP - Catur Pramono (Wahana Ilmuwan, 2016)
Livestock sub-sector, which is part of the agriculture sector is a strategic sector in supporting the regional and national economy. Availability of both imported and local meat is closely related to national food security. Fulfillment of meat to meet as a producer of animal protein consumption is useful in terms of health and human intelligence. UNICEF recognizes that nutrition is based on theprotein supply has contributed about 50% of economic growth in developed countries. The purpose of this study is to assess the performance good fodder mixing machine for mixing feed cows, goats, and poultry. The test results indicate that the machine is able to mix until homogeneous within 5 minutes 10 seconds to feed cattle with a mass of 2.8 kg, 3 minutes 6 seconds to feed the goats with a mass of 4.1 kg, and 1 minute 49 seconds for poultry feed with a mass of 5kg.